Constructing Commitment in Intimate Relationships: Mapping Interdependence in the Everyday Expressions of Commitment. (April 2014) - Weigel, Daniel J.; Ballard-Reisch, Deborah S.
By its very nature, relationship commitment is generated in the context of a relationship and becomes relational when it is communicated in some way to the other. This study investigated how expressions of commitment and commitment-related perceptions are interdependently connected among romantic partners. The authors derived and tested a dyadic cyclical model of the everyday expressions of commitment with a sample of 189 romantically involved couples. Results revealed that individual's level of commitment are associated with her or his own expressions of commitment, those expressions of commitment are noticed by the partners, and the partner's level of commitment is associated with those perceptions of the other's expressions of commitment. The research sheds light on the complex ways intimate couples experience and express commitment in their everyday lives.